Design and metrological evaluation of the new 5 MN hexapod-shaped multicomponent build-up system. (15th April 2016) - Palumbo, Stefano; Germak, Alessandro; Mazzoleni, Fabrizio; Desogus, Sergio; Barbato, Giulio
Abstract: The new 5 MN hexapod-shaped multicomponent build-up system (HSM-BUS) represents significant progress in the field of reference transducers in the high force range. As with any build-up system, the presented hexapod-shaped multicomponent force transducer can lead, not only to measure forces 5 times higher than the capacity of a each single uniaxial force transducer (UFT), but gives also information about the other components of the force vector and of the moment vector. Furthermore, the calibration of such types of multicomponent force transducer regards only the calibration of the signal outputs coming from each UFT and the calibration of the geometry of the system. In this work, an a priori evaluation of the expected uncertainty is performed. As a first approximation, the effects of the calibration uncertainties of UFTs and of the geometrical tolerances given on the construction drawing were considered. Subsequently, with a finite element simulation of the mechanical behavior of the 5 MN HSM-BUS under load, a mathematical model of elastic deformations has been evaluated and applied for evaluating and correcting the systematic errors due to the deformation of the geometry under load.